Rourke Baby Record 2014: Evidence-based tool for the health of infants and children from birth to age 5 - Riverin, Bruno (Can Fam Physician, 2015)
OBJECTIVE: To update the 2011 edition of the Rourke Baby Record (RBR) by reviewing current best evidence on health supervision of infants and children from birth to 5 years of age. QUALITY OF EVIDENCE: The quality of evidence was rated with the former (until 2006) Canadian Task Force on Preventive Health Care classification system and GRADE (grading of recommendations, assessment, development, and evaluation) approach. MAIN MESSAGE: New evidence has been incorporated into the 2014 RBR recommendations related to growth monitoring, nutrition, education and advice, development, physical examination, and immunization. Growth is monitored with the World Health Organization growth charts that were revised in 2014. Infants’ introduction to solid foods should be based on infant readiness and include iron-containing food products. Delaying introduction to common food allergens is not currently recommended to prevent food allergies. At 12 months of age, use of an open cup instead of a sippy cup should be promoted. The education and advice section counsels on injuries from unstable furniture and on the use of rear-facing car seats until age 2, and also includes information on healthy sleep habits, prevention of child maltreatment, family healthy active living and sedentary behaviour, and oral health. The education and advice section has also added a new environmental health category to account for the effects of environmental hazards on child health. The RBR uses broad developmental surveillance to recognize children who might be at risk of developmental delays. Verifying tongue mobility and patency of the anus is included in the physical examination during the first well-baby visit. The 2014 RBR also provides updates regarding the measles-mumps-rubella, live attenuated influenza, and human papillomavirus vaccines. CONCLUSION: The 2014 RBR is the most recent update of a longstanding evidence-based, practical knowledge translation tool with related Web-based resources to be used by both health care professionals and parents for preventive health care during early childhood. The 2014 RBR is endorsed by the Canadian Paediatric Society, the College of Family Physicians of Canada, and the Dietitians of Canada. National and Ontario versions of the RBR are available in English and French.